#TITLE_ALTERNATIVE# - PONIMAN KOSASIH (NIM 23105021); Pembimbing : Dr. Ir. Aditianto Ramelan dan Hady Efendy, S.T., M, DENY
From previous research, the oxidation of carbon steel as reinforced from alumina spinel castable refractory LAMJ-1 matrix takes places in 1150 degrees C with 6 hours holding time. Based on this research finding, it is performed a follow-up research by using steel reinforcing material, tin coated steel and stainless steels with 5 and 7 hours holding time in temperature 1150 degrees C. The result of residual reinforcing material diameter measurement on samples that is reinforced by carbon steel from firing output on T = 1150 degrees C with 5 and 7 hours holding time show diameter reduction as 7% and 16.6%. For samples reinforced by tin coated steel on 7 hours holding time occurs a reduction as 2.1%. Meanwhile, samples reinforced by 304 austenitic stainless steel is 1.1% and 2.4% 5 and 7 hours holding time, respectively. On sample reinforced by carbon steel took places addition of oxide layer thickness as large 22.2%. For sample reinforced by stainless steel was formed a gap between reinforcing steel and its matrix and occurred gap thickness addition as large 17.4% from 5 to 7 hours holding time. The SEM/EDS characteristics show the Fe weight fraction at oxide-matrix interface area for sample in steel reinforcement with 5 and 7 hours holding time as 47.6% and 67,3%, for sample reinforced by tin coated steel with 7 hours holding time is 64.4%. Meanwhile, sample reinforced by stainless steel, although it has gap between reinfrocing steel and matrix, in matrix area is available Fe content with weight fraction as large 42.5% and 83.6%. The XRD characteristic shows some occured phases on oxide layer for steel reinforced samples (5 hours) are Fe3O4, Fe2O3 and FeAl2O4, (7hours) Fe3O4, Fe2O3, FeAl2O4, and Mg(Fe,Al)2O4, Samples with lead-covered reinforcing steel (7 hours) FeO, Fe3O4, Fe2O3, FeAl2O4 and Mg(Fe,Al)2O4, (7 hours) Fe3O4, Fe2O3, MgCr2O3 and Cr2O3. A reduction in CCS value on steel reinforced samples with 5 and 7 hours holding time is 4.5%. Meanwhile, samples with stainless steel reinforcer took places an increase as 8%. For sample reinforced by tin caoted steel with 7 hours holding time is 25.26 Mpa, there is 12.3% reduction from CCS value of steel reinforced steel with same holding time.